2022
DOI: 10.1111/aen.12598
|View full text |Cite
|
Sign up to set email alerts
|

Acaricidal properties of the selected components, blends and essential oils of species of genus Protium (Burseraceae) against Tetranychus urticae (Acari: Tetranychidae)

Abstract: This study describes the chemical composition of essential oils from the leaves of Protium aracouchine and Protium giganteum, evaluates their acaricidal properties and investigates the role of monoterpenes and sesquiterpenes in toxicity to Tetranychus urticae by fumigation and residual contact. The chemical analyses revealed that spathulenol (32.2 ± 1.6%) and β-caryophyllene (27.3 ± 1.1%) were the major constituents of the P. aracouchine and P. giganteum oils, respectively. Both Protium oils were toxic to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…We found that DCY significantly reduced the feeding activity of TSSMs and these preliminary results suggest the potential of DCY as an agent of control for TSSMs infestations. Considering the constant threat to numerous crop plants due to TSSMs [ 31 ] and the continuous search for new and effective acaricides [ 32 , 33 , 34 ], we believe that DCY could be a good starting molecule to target guanine metabolism in the management of TSSMs infestations.…”
Section: Discussionmentioning
confidence: 99%
“…We found that DCY significantly reduced the feeding activity of TSSMs and these preliminary results suggest the potential of DCY as an agent of control for TSSMs infestations. Considering the constant threat to numerous crop plants due to TSSMs [ 31 ] and the continuous search for new and effective acaricides [ 32 , 33 , 34 ], we believe that DCY could be a good starting molecule to target guanine metabolism in the management of TSSMs infestations.…”
Section: Discussionmentioning
confidence: 99%